Hubungan Antara Lama Waktu Kerja Dengan Keluhan Muskuloskeletal Pada Penjahit Di Pasar Lolak - Tamarolo, Teti; Evert Mautang, Theo Welly; Palilingan, Richard Andreas (Poltekkes Kemenkes Jambi, 2025)
Background: This study was motivated by the high risk of musculoskeletal complaints in tailors due to non-ergonomic working postures and long working hours. The purpose of the study was to determine the relationship between working hours and musculoskeletal complaints in tailors at Pasar Lolak. Methods: Data were collected using a questionnaire on respondent characteristics and the Nordic Body Map (NBM) to measure musculoskeletal complaints. Data analysis used the Chi-Square test. Results: The majority of tailors at Pasar Lolak were aged 36-45 years, with more than 10 years of work experience and most were female. Most tailors worked for 8-10 hours per day, with high category musculoskeletal complaints (71-91 on the NBM scale) more often found than the moderate category (50-70). Bivariate analysis showed a significant relationship between working hours and musculoskeletal complaints (p = 0.002 < 0.05). Conclusion: There is a significant relationship between working hours and musculoskeletal complaints in tailors at Pasar Lolak. It is recommended that tailors pay attention to working hours and working postures to prevent musculoskeletal complaints.